A Short Review on Advances in Early Diagnosis and Treatment of Ischemic Stroke: Advancements in Diagnosis and Treatments of Ischemic Stroke - Sun, Bin; Wang, Zhigang (Galen Medical Journal, 2023)
Ischemic stroke is a leading cause of morbidity and mortality worldwide, necessitating advancements in early diagnosis and treatment modalities. This review aims to provide an overview of recent advances in the early diagnosis and treatment of ischemic stroke, highlighting the importance of the potential impact on patient outcomes. Recent advancements have focused on various aspects of stroke care, including imaging techniques, laboratory testing, telemedicine and mobile technology, intravenous thrombolysis, mechanical thrombectomy, and collaborative systems. Advances in imaging techniques have played a pivotal role in the early diagnosis of ischemic stroke. Computed tomography perfusion imaging, advanced magnetic resonance imaging (MRI) techniques, multimodal imaging, and automated image processing tools have greatly improved the ability to assess the extent of ischemic injury. Laboratory testing has seen significant progress in identifying biomarkers associated with ischemic stroke. High-sensitivity cardiac troponin assays have improved our understanding of the cardiac component of stroke. Additionally, biomarkers such as S100B, glial fibrillary acidic protein, and neuron-specific enolase have shown promise in assessing stroke severity and prognosis. Mobile applications and wearable devices facilitate stroke symptom recognition, risk assessment, and prompt medical attention. The development of tenecteplase, a modified form of tissue plasminogen activator, has enhanced clot-dissolving efficacy. Collaborative systems, including regional stroke systems of care and telestroke networks, have optimized communication and coordination among healthcare providers. Interoperable electronic health records streamline information exchange and facilitate prompt decision-making. Mobile communication technologies enhance real-time collaboration, involving all stakeholders in stroke care. Future directions focus on artificial intelligence and machine learning algorithms for stroke diagnosis and risk assessment. Wearable devices and remote monitoring may enable continuous monitoring of stroke-related indicators. Overall, advances in early diagnosis and treatment of ischemic stroke can enhance stroke care, reduce treatment delays, and improve patient outcomes.